Signaling through the G-protein-coupled receptor Rickets is important for polarity, detachment, and migration of the border cells in Drosophila - Anllo, Lauren (Dev Biol, 2016)
Cell migration plays crucial roles during development. An excellent model to study coordinated cell movements is provided by the migration of border cell clusters within a developing Drosophila egg chamber. In a mutagenesis screen, we isolated two alleles of the gene rickets (rk) encoding a G-protein-coupled receptor. The rk alleles result in border cell migration defects in a significant fraction of egg chambers. In rk mutants, border cells are properly specified and express the marker Slbo. Yet, analysis of both fixed as well as live samples revealed that some single border cells lag behind the main border cell cluster during migration, or, in other cases, the entire border cell cluster can remain tethered to the anterior epithelium as it migrates. These defects are observed significantly more often in mosaic border cell clusters, than in full mutant clusters. Reduction of the Rk ligand, Bursicon, in the border cell cluster also resulted in migration defects, strongly suggesting that Rk signaling is utilized for communication within the border cell cluster itself. The mutant border cells show defects in localization of the adhesion protein E-cadherin, and apical polarity proteins during migration. E-cadherin mislocalization occurs in mosaic clusters, but not in full mutant clusters, correlating well with the rk border cell migration phenotype. Our work has identified a receptor with a previously unknown role in border cell migration that appears to regulate detachment and polarity of the border cell cluster coordinating processes within the cells of the cluster themselves.